Yes man [videorecording (DVD)] - Reed, Peyton; Carrey, Jim, 1962-; Deschanel, Zooey, 1980-; Cooper, Bradley; Wallace, Danny (Warner Home Video, 2009)
Carl Allen signs up for a self-help program based on one simple principle: say yes to everything...and anything. Unleashing the power of 'yes' transforms Carl's life in amazing and unexpected ways, but he soon discovers that embracing every opportunity might just become too much of a good thing.